2020
DOI: 10.1111/os.12689
|View full text |Cite
|
Sign up to set email alerts
|

No Learning Curve of the Direct Superior Approach in Total Hip Arthroplasty

Abstract: ObjectivesTo assess the learning curve of the direct superior approach (DSA) for total hip arthroplasty (THA) and to compare surgical, clinical, and radiological results with a matched control group using the mini posterior approach (MPA).MethodsA prospective cohort study was performed from October 2016 to May 2017 including our first 52 patients undergoing THA using the DSA. Patients with primary osteoarthritis or osteonecrosis and a body mass index (BMI) < 35 who were eligible for surgery were included. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(40 citation statements)
references
References 43 publications
0
36
0
2
Order By: Relevance
“…Суть данных хирургических доступов заключается в использовании интервала между m. gluteus minimus и m. piriformis с сохранением большей части наружных ротаторов и абдукторов бедренной кости [22]. Однако при использовании direct superior чаще всего происходит мобилизация сухожилий m. piriformis и m. gemelleus superior, остальные ротаторы защищены благодаря уменьшенному объему движения бедренной кости во время операции (40° приведения, 40° сгибания, 40° внутренней ротации) [23]. Доступ SuperCap предполагает сохранение наружных ротаторов и опил шейки in situ после обработки канала бедренной кости, т.е.…”
Section: Direct Superior Approach/supercapunclassified
See 1 more Smart Citation
“…Суть данных хирургических доступов заключается в использовании интервала между m. gluteus minimus и m. piriformis с сохранением большей части наружных ротаторов и абдукторов бедренной кости [22]. Однако при использовании direct superior чаще всего происходит мобилизация сухожилий m. piriformis и m. gemelleus superior, остальные ротаторы защищены благодаря уменьшенному объему движения бедренной кости во время операции (40° приведения, 40° сгибания, 40° внутренней ротации) [23]. Доступ SuperCap предполагает сохранение наружных ротаторов и опил шейки in situ после обработки канала бедренной кости, т.е.…”
Section: Direct Superior Approach/supercapunclassified
“…MPA [18,23,30,37,45,46] 220 1,4 -0,5 -4,1 -0, Показатели кровопотери, продолжительности пребывания в стационаре, функциональные результаты по шкале HHS через 3 и 12 мес. между рассматриваемыми техниками статистически не различались.…”
Section: таблица 2 результаты по Hhs через 3 месяца после тотального эндопротезированияunclassified
“…T otal hip arthroplasty (THA) is the most extensively employed artificial joint replacement surgery 1,2 . Periprosthetic joint infection (PJI) is one of the most challenging complications after THA 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Shorter length of hospital stay and enhanced recovery with higher functional scores were recorded in comparison with the PLA ( 14 - 19 ). Contrary to the DAA, the learning curve seems to be limited ( 10 - 11 , 20 ). Whether a limited learning curve will be found outside specialist centers remains to be proven.…”
mentioning
confidence: 93%
“…In comparison with the PLA, the DSA should therefore improve implant stability. Outcomes of THA with the DSA have shown that reliable implant positioning can be obtained with a low early complication rate ( 11 - 13 ). Shorter length of hospital stay and enhanced recovery with higher functional scores were recorded in comparison with the PLA ( 14 - 19 ).…”
mentioning
confidence: 99%